Credit Supply Shocks and Firm Dynamics: Evidence from Brazil - Samuel Bazzi; Marc-Andreas Muendler; Raquel F. Oliveira; James Rauch; James E. Rauch (Center for Economic Studies and ifo Institute (CESifo), 2023)
We explore how financial constraints distort the entry decisions among otherwise productive entrepreneurs and limit growth of promising young firms. A model of liquidity-constrained entrepreneurs suggests that the easing of credit constraints can induce more entry of firms with greater long-run growth potential than the easing of conventional entry barriers would bring about. We explore this growth mechanism using a large-scale program to expand the supply of credit to small and medium enterprises in Brazil. Local credit supply shocks generate greater firm entry but also greater exit with no effect on short-run employment growth in the formal sector. However, credit expansions increase average capability among entering firms, which enter at larger size, survive longer, and grow faster. These firm dynamics are more pronounced in areas with weaker credit markets ex ante and consistent with local bank branches using cheap targeted credit lines to expand lending more broadly. Our findings provide new evidence on the general equilibrium effects of credit supply expansions.
Keywords: D21; D22; D92; L25; L26; M13; O12; 330; credit constraints; entry barriers; growth barriers; startups